Female breast cancer classification using immunohistochemistry biomarkers staining in Botswana - Andrew Khulekani Ndlovu; Ishmael Kasvosve; Patricia S. Rantshabeng; Kirthana Sharma; Dhiren Govender; Richard Naidoo (BMC Cancer)
Abstract Breast cancer remains the most diagnosed cancer among women world-wide and a leading cause of cancer-related deaths accounting for 15% of deaths in 2018. Worldwide, the incidence increased from 1.4 million in 2011 to over 2 million in 2018 with a concomitant increase in mortality from 458,400 to 626,679 in the same period. Low- and middle-income countries, such as Botswana, have a disproportionate burden of breast cancer incidence and mortality and there is an urgent need to characterise the unique tumour molecular profiles that may be influencing mortality in these populations. Methods A retrospective study of 125 archived mastectomy specimens (from 2006 to 2009) from women with breast cancer in Botswana was conducted. We determined molecular characteristics of breast cancers by carrying out four immunohistochemistry (IHC)classification (PR, ER, HER2 receptors and Ki 67), cytokeratin 5/6 and EGFR1.Statistical software STATA and SPSS were used to determine the relationship between histology, IHC of biomarkers of interest. Results Out of 125 breast cancer tissues, the distribution of molecular subtypes were as follows: Luminal A (44/125; 35.2%), Luminal B (and TNBC (23/125; 18,4%), HER2 Enriched (17/125; 13.6%), and Luminal B HER2 Enriched (9/125; 7.2%), Basal (9/125; 7.2%), and CK5/6 was expressed by 12.8% (16/125) of tumours. Furthermore 6% of the tumours were basal positive luminal tumours. Morphological 76% of tumours were IDC-NOS and 24% were special type, majority were grade 2 (40%) followed by grade 1(30.4%), grade 3 (23.2%) was and mucinous types were 6.4%. Clinical staging and tumour involvement data were incomplete. Conclusion The discovery of basal positive luminal breast tumours in women from Botswana original not accounted for in the four distinct molecular subtype calls for an expanded antibody panel 6-IHC panel) in order to stratify women of African descent patients into good/poor prognostic groups. Characterising tumour subtypes will better inform optimal therapeutic regimens for women with breast cancer in Botswana.